Osteochondral femoral anterior cruciate ligament avulsion in a 13 years old patient: a case report - Yamanih, Al-Muthana M. A.; Alshaweesh, Mumen M.; Shari, Naser F.; Alannaz, Nizar A. A.; Odat, Mohannad A. (International Journal of Research in Orthopaedics, 2023)
Anterior cruciate ligament (ACL) injury, is one of the most common injuries occurring in young active patients. Regarding pediatric group, ACL avulsion is the most common form of injury in contrast to adults, whose injury pattern is described as mid-substance injury. Tibial avulsion of ACL is the most common form of avulsion in pediatrics, while osteochondral femoral avulsion is considered rare entity. Our case report is about a 13-year-old pediatric male patient, sustained injury over his right knee during soccer game in March 2023. Immediately after injury, patient described having giving way, associated with severe pain. 2 days after initial injury, patient and his family noticed that his giving way continued to occur. Upon presentation to clinic, physical examination raised suspicion to have ACL injury, magnetic resonance imaging (MRI) and computed tomography (CT) confirmed osteochondral femoral origin avulsion of ACL. After reviewing literature, decision was to go for ACL repair through femoral origin avulsion fracture fixation using suture pullout technique secured with two anchors fixed through lateral femoral cortex to avoid physis injury while reaming femoral and tibial tunnels used for graft reconstruction. On follow up, excellent functional outcome regarding knee stability and range of motion. We conclude that although femoral-sided repair using suture pullout technique carried higher risk of failure than ACL reconstruction, this method shows excellent functional outcome, and can be used in cases of osteochondral femoral avulsion in pediatric group to avoid risk of physis injury in such age group.